2015
DOI: 10.1007/s13410-015-0414-0
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 +49A/G gene polymorphism and type 1 diabetes mellitus in the Chinese population: a meta-analysis of 2238 subjects

Abstract: Previous studies reported that cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) +49A/G gene polymorphism is correlated with type 1 diabetes mellitus (T1DM) risk. However, their results remain disputable. This study aims to discuss the relationship between CTLA-4 +49A/ G gene polymorphism and T1DM in a Chinese population. The current meta-analysis involved 2238 participants from seven individual studies. The pooled odds ratio (OR) and its corresponding 95 % confidence interval (95 % CI) were assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…46,47 Multiple studies have noted predisposing role for minor G allele of this polymorphism for CD 18 and T1D. [13][14][15][19][20][21][22][23][24] Two studies; Mora et al, Naluai et al 16,17 have observed the higher risk of CD in individuals bearing the wild-type A allele of this polymorphism. On the other hand, some have not reported any significant association between this polymorphism with the occurrence of CD 12,13 and T1D.…”
Section: Cytotoxic T-lymphocyte Associated Proteinmentioning
confidence: 99%
“…46,47 Multiple studies have noted predisposing role for minor G allele of this polymorphism for CD 18 and T1D. [13][14][15][19][20][21][22][23][24] Two studies; Mora et al, Naluai et al 16,17 have observed the higher risk of CD in individuals bearing the wild-type A allele of this polymorphism. On the other hand, some have not reported any significant association between this polymorphism with the occurrence of CD 12,13 and T1D.…”
Section: Cytotoxic T-lymphocyte Associated Proteinmentioning
confidence: 99%
“…At present, the cause of T1DM is still unknown, and genetic susceptibility, a diabetogenic trigger, and high exposure to an antigen are believed to be involved [4]. A meta-analysis involving 2238 T1DM participants showed that individuals had a higher risk for T1DM with the G allele of CTLA-4 +49A/G gene polymorphism [5]. Arroyo-Jousse et al [6] found that T1DM patients showed a higher TNFa gene promoter methylation compared with control subjects [p=0.00008].…”
Section: Introductionmentioning
confidence: 99%